Pemetaan situasi dan kondisi kebahasaan dalam mendukung keberhasilan program BIPA di Timor Leste - Amanat, Tri (Badan Pengembangan Bahasa dan Perbukuan, 2019)
One step to improve the function of Indonesian language into an international language is done through the development of Indonesian language teaching programs for foreigners (BIPA) in various friendly countries, including Timor Leste. Until now Timor Leste is one of the countries with the most requests for sending BIPA teachers. Therefore certain steps are needed to support the success of this program, one of which is by conducting a study related to the situation and conditions of the language. This study aims to; Describe the situation and conditions of language that exists in Timor Leste both in the realm of government policy and the real conditions that exist in society. Mapping the potential and barriers to the development of Indonesian in East Timor. This study uses qualitative methods. Data acquisition is done through document analysis, field observations, and interviews. The results of the study indicate that East Timor is a multilingual community. In macro terms, there are several regulations that can support the development of BIPA, however, there are also some that can hamper. In micro terms, Indonesian is still considered familiar by certain groups but in general, the younger generation of Timor Leste (especially those born after independence) have many who do not understand/know bahasa Indonesian.